2021
DOI: 10.1186/s12903-020-01364-4
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration and sealing for managing non-cavitated proximal lesions: a systematic review and meta-analysis

Abstract: Background Infiltration and sealing are micro-invasive treatments for arresting proximal non-cavitated caries lesions; however, their efficacies under different conditions remain unknown. This systematic review and meta-analysis aimed to evaluate the caries-arresting effectiveness of infiltration and sealing and to further analyse their efficacies across different dentition types and caries risk levels. Methods Six electronic databases were searche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
(154 reference statements)
2
13
0
1
Order By: Relevance
“…Te caries process can be controlled by mechanical plaque control, efective oral hygiene, fuoride and antimicrobial application, and avoiding sugar intake between meals [6,7]. Resin infltration of WSLs and sealing of noncavitated lesions as a treatment option have been supported by several studies [51,56,59]. Tis method represents the minimal invasive option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te caries process can be controlled by mechanical plaque control, efective oral hygiene, fuoride and antimicrobial application, and avoiding sugar intake between meals [6,7]. Resin infltration of WSLs and sealing of noncavitated lesions as a treatment option have been supported by several studies [51,56,59]. Tis method represents the minimal invasive option.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, sealing the noncavitated carious lesion has been shown to stop lesion progression in vivo and in vitro effectively [51,[56][57][58]. A proximal carious lesion can be sealed after separating the afected tooth to reach the lesion.…”
Section: Sealing Of Noncavitated Caries Lesionsmentioning
confidence: 99%
“…Meta-analysis assessing the effectiveness of resin infiltration in arresting the progress of non-cavitated proximal lesions have found them to be highly efficacious in permanent teeth when the lesions extend into the enamel and outer third of dentin [ 125 , 126 , 127 , 128 , 129 , 130 ]. For permanent teeth, the risk of caries progression was shown to be significantly lower in infiltrated lesions (4–14%) relative to control (42–48%) over three years [ 131 , 132 ] and Paris et al found the seven-year rate of progression to be 9% for infiltrated lesions vs 45% for control lesions [ 133 ].…”
Section: Resin Infiltration For the Management Of Carious Lesionsmentioning
confidence: 99%
“…For primary teeth, early meta-analysis found the data regarding RI efficacy inconclusive, due to the heterogeneity of study designs and settings [ 125 , 126 , 127 ]. A meta-analysis by Chen et al in 2021 concluded that although more clinical studies were needed, findings from current studies were encouraging and resin infiltration is efficacious in arresting decay progress in primary teeth for 12–24 months [ 130 ]. Based on these studies, the therapeutic effect of RI was found to range from 21% [ 134 , 135 ] to 38% [ 136 ].…”
Section: Resin Infiltration For the Management Of Carious Lesionsmentioning
confidence: 99%
“…As a result, the window for penetration of bacterial toxins into the hard tissues and the bacteria producing them is closed. The result is inhibition of the decalcification process and caries development [ 19 , 20 ]. An infiltrant is a substance based on polymeric resins, capable of penetrating tissues due to capillary forces.…”
Section: Introductionmentioning
confidence: 99%